Manejo terapéutico de los trastornos vesiculares en gestantes - Mora Amoroso, Emilia Gisselle (2023)
ABSTRACT: Gallbladder disorders in pregnancy are currently considered one of the most common non-obstetric abdominal pathologies, being a public health problem. The presence of gallstones is more frequent in pregnant women than in non-pregnant women due to the physiological and hormonal changes experienced by women at this stage, which puts at risk maternal-fetal wellbeing, affecting the normal course of pregnancy. The delay in managing these pathologies implies increased morbidity in this population group. The objective was to conduct a literature review on the therapeutic management of vesicular disorders in pregnant women. The methodology used was Bibliographic research with a qualitative approach, descriptive in scope, non-experimental, cross-sectional, and retrospective chronology, with research published in the last five years using 50 documents with scientific validity obtained from regional and high-impact databases such as PubMed, Web of Science, Dialnet, Scielo, Scopus, Cochrane Library, ScienceDirect, Lilacs, Medline, Medigraphic, Uptodate. The result shows that there is controversy in the treatment choice since there are several therapeutic options, including conservative management and surgical approaches. Laparoscopic cholecystectomy is beneficial and safe in any trimester of gestation, with low maternal-fetal complication rates of 3.5%. In conclusion, Laparoscopic cholecystectomy is a safe method of choice for patients with symptoms and or complications of biliary pathology, while the conservative approach is reserved for asymptomatic patients. Keywords: Gallbladder disorders, pregnant women, therapeutic management, cholecystectomy, maternal-fetal complications